(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The days when only specialists worked with programs and the functionality was the most important have long passed. In today's competitive environment, an important marketing component is reliability in which the only tangible part of the program, the interface, plays a large role. Purely psychological, it is important for the users' visibility, correctness and can even be argued, friendliness. This is determined by the elements of visibility and components' location in intuitively expected places, design integrity, tone and choice of characteristic elements which, together, create a feeling of sympathy or antipathy from the software user. Regularities, which ultimately determine the user's subconscious reactions, are found in natural formations - from the most basic proportions of plants to more sophisticated self-arranged compositions. The harmony of the structures of natural systems, that is, their internal organization, is subject to certain mathematical laws. Objective world stable stationary states corresponding to particular figures, called generalized Golen Ratios. These figures are all the structure of the invariant, which are embodied by the dialectic structure of the world and the different variations that can be observed at every step of nature. It is important to note that with the generalized Golden Ratio, not only is the well-known ratio of 1:1,618 understood, but a whole line of relationships, where like in music, a single major or minor note can be played, and another can stand out from the whole ensemble. The main applications of the Goden Ratio in interface design are space division, caption-font size ratios, restrictive areas (buttons), title queue length, color tone saturation ratio, and cell location coordinates. In this paper, we propose certain recomendations for the development of a user - friendly interface. These recommendations suggest uses in the software developer training process for non-design specialty students; target group - programmers, computer specialists, and IT project managers. The article does not address the development of graphic design tools and their functionality.